A pair of tess planets spanning the radius valley around the nearby mid-m dwarf ltt 3780 - Cloutier, Ryan (2020)
We present the confirmation of two new planets transiting the nearby mid-M dwarf LTT 3780 (TIC 36724087, TOI-732, V = 13.07, Ks = 8.204, Rs=0.374 R , Ms=0.401 M , d=22 pc). The two planet candidates are identified in a single TESS sector and are validated with reconnaissance spectroscopy, ground-based photometric follow-up, and high-resolution imaging. With measured orbital periods of Pb = 0.77 days, Pc = 12.25 days and sizes rp,b = 1.33 ± 0.07 R⊕, rp,c = 2.30 ± 0.16 R⊕, the two planets span the radius valley in period-radius space around low mass stars thus making the system a laboratory to test competing theories of the emergence of the radius valley in that stellar mass regime. By combining 63 precise radial-velocity measurements from HARPS and HARPS-N, we measure planet masses of mp,b = 2.62+0.48 −0.46 M⊕ and mp,c = 8.6 +1.6 −1.3 M⊕, which indicates that LTT 3780b has a bulk composition consistent with being Earth-like, while LTT 3780c likely hosts an extended H/He envelope. We show that the recovered planetary masses are consistent with predictions from both photoevaporation and from core-powered mass loss models. The brightness and small size of LTT 3780, along with the measured planetary parameters, render LTT 3780b and c as accessible targets for atmospheric characterization of planets within the same planetary system and spanning the radius valley.